Types of Translation Errors from Indonesia Language into English in Pharmacy Journal Articles - Widya Dara Anindya; Aqiana Eka Yonatri (RETORIKA: Jurnal Ilmu Bahasa, 2022)
The study analyzed the types of errors based on ATA Error Categories version 2021 on the three submitted journal articles translated by lecturers of Clinical Pharmacy and Pharmacy Community of Akademi Farmasi Surabaya. It aimed to find the types of errors often made by pharmacy lecturers in translating the articles from the Indonesian language into English so that the results of this study can help them identify and avoid errors in translation. The study used the descriptive qualitative, using the content analysis method. The objects of this study were three journal articles in the Indonesian language (ST) and English (TT). The data focused on the translation errors based on ATA Error Categories in the words or phrases level. The results showed there were 14 types of errors found, namely: literalness (31.05%), usage (22.22%), punctuation (7.84%), terminology (7.52%), verb form (6.86%), grammar (6.54%), capitalization (3.59%), parts of speech (3.59%), syntax (3.27%), style (2.94%), register (2.29%), omission (1.31%), cohesion (0.65%), and ambiguity (0.33%). The study recommended that translators have sufficient knowledge about the target language mechanics, produce clear renditions of the source text, and maintain the writing quality of the target text.